Quality of Life and its Relation with Psychological Loneliness and Depression Among the Teachers of the Ministry of Education in Ajloun Province- Jordan - Almomani, Lina Mahmoud Mohammad (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the quality of life and its relationship to psychological unity and depression among teachers of the Ministry of Education in Ajloun Governorate, and the study used the descriptive analytical approach, the study population consisted of teachers of the Ministry of Education in Ajloun Governorate, the study sample consisted of (387) teachers in The Ministry of Education in Ajloun Governorate, they were randomly selected, and to achieve the goals of the study, the researcher designed a questionnaire as a tool to collect data from members of the study sample, and the study reached the most important results: The study showed: There is an average degree in the level of quality of life for teachers of the Ministry of Education in the province Ajloun, the presence of an average degree in the level of psychological unity among the teachers of the Ministry of Education in Ajloun Governorate, the presence of a degree of level of depression among the teachers of the Ministry of Education in Ajloun Governorate, and the study also showed an inverse relationship between the quality of life and psychological Loneliness, and the existence of an inverse relationship between the quality of life and depression, Based on the results, the study recommended the following: Developing a system of rewards and incentives for advertisers to improve their living conditions, to satisfy their needs in order to reach a neighborhood Ah good. Reducing the academic burden and other activities by increasing the number of teachers in schools, reducing the administrative tasks assigned to teachers, especially new teachers, and developing training and qualification programs for them to be better able to face psychological unity and depression, conducting more studies on quality of life, psychological unity, and depression among teachers to reveal the extent of Its spread and its negative effects on the educational process.